Sosialisasi Hukum Tindak Pidana Penganiayaan di Kelurahan Paria, Kecamatan Majauleng, Kabupaten Wajo - Andi Dadi Mashuri; Anugrah Dwi Saputra; Andi Nail Ijlal Zaki; Arsy Muqtadir; Ismail Ali (Compile Journal of Society Service, 2025)
According to data from the Ministry of Law and Human Rights (Kemenkumham), there were approximately 10,000 cases of abuse recorded throughout Indonesia in 2022. This figure indicates that abuse is a serious problem that requires appropriate legal action. This demonstrates the need for more intensive criminal law outreach at the sub-district level to provide public understanding of the legal consequences of such actions. As a form of community service, criminal law outreach regarding abuse was carried out in Paria Village, Majauleng District, Wajo Regency, through outreach and discussion methods. This outreach covered 1) the legal basis for abuse, 2) types of abuse, 3) legal consequences of abuse, and 4) efforts to eradicate abuse. This activity aims to raise public awareness of the importance of respecting human rights and understanding that abuse is a legal violation that can be subject to criminal sanctions. The results of this outreach have succeeded in increasing public understanding of the law on criminal acts of assault.